Construction of 3D environment from 2D RGB images and depth information - Shakir, Redwanul Islam; Hossain, Sarwar; Khan, Mehrab Mohsin; Mayaz, Md Ishtiaq Enam (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.